Prosedur Administrasi Pengangkutan Limbah Bahan Berbahaya dan Beracun Pada PT XX Jakarta - Karomah, Nurul Giswi; Amalia, Fadwa (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2022)
This research was conducted to find out how the administrative procedures for transporting B3 waste at PT Global Mandiri Marine, the purpose of this study was to find out the description of the procedures and constraints and alternative solutions in solving the problem. This research method is descriptive qualitative with data collection techniques through literature, interviews and observation, namely direct observation of the object under study. The obstacles that occurred in the Administration Procedure for the Transport of B3 Waste at PT Global Mandiri Marine, there were errors in inputting the weight and type of waste, errors in providing documents, and leaks of B3 waste. The solutions implemented are still not effective because several alternatives sometimes still use estimates of the weight and type of B3 waste, raising awareness among parties regarding the correct administration of B3 waste transportation in accordance with applicable regulations is to calculate the weight of the waste directly using a scale. and the provision of festronic data or manifests is given truthfully, and uses good quality for B3 waste packaging, so that the transportation of B3 waste can run properly and according to company procedures.